Dietary fatty acids and cardiovascular disease: A review - Prates, Raquel Eccel; Von Frankenberg, Anize Delfino; Rodrigues, Ticiana da Costa (Clinical and Biomedical Research, 2015)
Fatty acids (FAs) can be classified into saturated (SFA), unsaturated (poly- or monounsaturated) and trans FA. Recent studies have found that both the quantity and quality of dietary FAs may influence their role in metabolic pathways. Due to their chemical composition, some FAs play a major role in the development and progression of cardiovascular disease. This is especially true for SFA and n-3 polyunsaturated fatty acids, which include marine eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). The proinflammatory effects of high SFA intake may increase the risk of atherosclerosis. On the other hand, dietary n-3 intake may reduce the risk of cardiovascular disease by decreasing atherosclerosis, inflammation, and thrombotic processes. The goal of this study was to review the current literature on the role of FA intake in the prevention and risk of cardiovascular disease.